Ustadz Adi Hidayat Bilingual Da’wa Message in Japan: Youtube Video Content Analysis - Fahmi, Lukman; Amiatun Nuryana (Proceedings of International Conference on Da'wa and Communication, 2022)
Many ustadz in Indonesia preach in various ways. One example is Ustadz Adi Hidayat's da'wah in Japan, where he used bilingualism to reach out to Muslim congregations in one of Japan's mosques. This research focuses on examining the message content of the da'wah and the use of bilingualism in the da'wah delivered by Ustadz Adi Hidayat in Japan. There are two types of content messages: a sharia message and two creed messages, which include three da'wah messages from Ustadz Adi Hidayat's YouTube video in Japan: (1) how Allah's commands are revealed in stages, (2) how Allah's commands are revealed simultaneously rather than gradually, and (3) the wisdom and benefits of carrying out Allah's commands sequentially. Moreover, Ustadz Adi Hidayat da'wah is based on code-switching and code-mixing from English to Indonesian. Ustadz Adi Hidayat used bilingualism in his da'wah in Japan to make it easier for him to convey the message content of the da'wah and for the audience to receive messages conveyed by Ustadz Adi Hidayat.